De-evolution of expectations for evidence-based practices in public education in the United States - Brady, Michael P.; Hazelkorn, Michael (Education Policy Analysis Archives, 2019)
Public education in the United States has been undergoing a shift from an empirical tradition in which practices and policies are derived from research, practice, reflection, and implementation. In this empirical tradition, professionals embrace a culture and commitment to evidence-based practices (EBPs) and expect that practices and policies in the field are supported by rational, data-driven models. In this paper, we present an argument and three cases that illustrate how educators have been undergoing a gradual shift away from empiricism toward a de-evolution of EBP. We propose that this gradual shift is based on a political-social context, in which practices and policies are implemented using the language of an accountability model of reform, in which national and state regulations, and accreditation bodies, establish expectations often devoid of an empirical basis for the practices they mandate.